2004
DOI: 10.1051/forest:2004023
|View full text |Cite
|
Sign up to set email alerts
|

Growth of a poplar short rotation coppice under elevated atmospheric CO2 concentrations (EUROFACE) depends on fertilization and species

Abstract: -Growth and woody biomass production of three Populus species (P. nigra L. clone Jean Pourtet, P. alba L. clone 2AS-11 and P. × euramericana clone I-214), were followed during the first growing season after coppice of a short rotation coppice culture exposed to elevated atmospheric CO 2 concentrations by means of Free-Air Carbon dioxide Enrichment (FACE), and to a nitrogen (N) fertilization treatment. FACE significantly increased the number of shoots per stool, but did not significantly increase height nor tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
(64 reference statements)
1
9
0
Order By: Relevance
“…We can argue that in soil under elevated [CO 2 ] this down regulation did not occur and the poplar uptake remained high. This hypothesis is confirmed by the findings of Liberloo et al (2004) that in the same year 2002 observed a positive effect of the interaction of elevated [CO 2 ] and N fertilization in plant production.…”
Section: Soil N Availability and Mineralization-immobilization Processessupporting
confidence: 86%
“…We can argue that in soil under elevated [CO 2 ] this down regulation did not occur and the poplar uptake remained high. This hypothesis is confirmed by the findings of Liberloo et al (2004) that in the same year 2002 observed a positive effect of the interaction of elevated [CO 2 ] and N fertilization in plant production.…”
Section: Soil N Availability and Mineralization-immobilization Processessupporting
confidence: 86%
“…Fine root turnover is therefore considered as one of the major pathways of new carbon entering soil C pools. These findings contrast Liberloo et al (2004Liberloo et al ( , 2005; unpublished (a) and from Gielen et al (2001Gielen et al ( , 2003, and Liberloo et al (2006) with results from noncoppiced forests, such as the sweetgum stand , where fine root production of sweetgum trees almost doubled in elevated [CO 2 ], contributing to a sustained increase in NPP. A strong above-ground biomass response in the first year was replaced by an equally strong response of fine root productivity from the second year onwards.…”
Section: Growth Dynamics and Productivitymentioning
confidence: 59%
“…Data represent continuous measurements of trees growing in permanent growth plots and are adapted from Calfapietra et al . (2003b), Liberloo et al . (2004, 2005); unpublished (a) and from Gielen et al .…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations